Estimation of Handgrip Strength and its Correlations with Selected Anthropometric Variables and Performance Tests in Indian Interuniversity Female Field Hockey Players - Shyamal Koley; Amandeep Kaur (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2017)
Background: Handgrip strength is used as an indicator of total physical strength which is a prerequisite of physical performances in major competitions in any sport. Field hockey is an endurance sport where physical strength, techniques and tactics are essential. Thus estimation of handgrip strength of female field hockey players is needed to enhance the performances. Methods: The purpose of this study was of two-fold: first, to estimate the handgrip strength of Indian inter-university female field hockey players and, second, to search the correlations of it with selected anthropometric variables and performance tests. To serve this purpose, a total of five anthropometric variables, viz. height, weight, BMI, percent body fat and upper arm circumference, two performance tests, viz. sit and reach test and vertical jump test, and dominant and non-dominant handgrip strength were measured on purposely selected 121 Indian inter-university female hockey players aged 18-25 years collected from the inter-university competition organized in Guru Nanak Dev University, Amritsar, Punjab, India during March, 2014. The subjects were further divided as per their playing positions, viz. goalkeepers (n=05), strikers (n=67) and defenders (n=49).\ Results: In results, one way analysis of variance showed statistically no significant between-group differences among these three sets of players. Significantly positive correlations (p ≤ 0.05 - 0.01) of dominant handgrip strength were found only with non-dominant handgrip strength in the Indian inter university female field hockey players. Conclusions: The study carries immense practical applications and should be useful in future investigation on player selection, talent identification in field hockey and training program development.